Metallization process for alumina substrates - Mohd Shapee, Sabrina; Alias, Rosidah; Ibrahim, Azmi; Yahya, Mohamed Razman; Awang Mat, Abdul Fatah; Hashim, Mansor (Universiti Putra Malaysia Press, 2005)
Alumina substrate has been widely used as a substrate material for ceramic packaging technology. This material shows the excellent combination of electrical, mechanical and thermal properties. Metallization process is a process used for making electrically conductive interconnects on insulating substrate like alumina substrates. Three fundamental methods of metallizing alumina substrates include thick film, thin film and copper metallization technology. In this paper, the RF magnetron sputtering method was used to deposit copper conductor on alumina substrate surface.